Experiments on ZnO:Ni thin films with under 1% nickel content. (June 2015) - Rajeh, S.; Mhamdi, A.; Khirouni, K.; Amlouk, M.; Guermazi, S.
Abstract: In this paper, we present experimental results on doping under 1% of Ni into ZnO sprayed thin films to create a ZnO intrinsic layer and evaluate the resulting beneficial effects. X-ray diffraction (XRD) analysis showed that undoped and Ni-doped ZnO films crystallized into a hexagonal structure, where the crystallites preferentially oriented along the (002) direction that was perpendicular to the substrate. The optical transmittance was found to exceed 80%. An investigation of the variation in the band gap with the x =[Ni]/[Zn] ratio showed that the energy gap decreased from 3.29 eV to 3.22 eV as x increased from 0% to 0.25% and then increased to 3.28 eV at x =1%. The Urbach energy E u, the refractive index and the extinction coefficient were found to depend on the Ni content. The refractive index could be described as a single oscillator using the Wemple–DiDomenico model, which was used to determine the dispersion parameters and the high-frequency dielectric constant. Highlights: The sample with a 0.5% Ni content exhibited the highest texture coefficient for the (002) diffraction peak. The energy gap increased to 322 eV for the sample with a ZnO:Ni ratio of 0.25%. ZnO sprayed thin films with Ni contents in the 0.5–1.0% range exhibited intrinsic type conductivity.